Discourses of Inverted Yield Curve and the Reaction on US Stock Markets - Rofi, M Akhsanur (Research Center and Case Clearing House PPM School of Management, 2021)
An outlook model to predict future economic growth is crucially important for government, financial institution, corporate, investor, as well as household. An inverted yield curve has been trusted for long time as a prediction for economic recession. But current development showed that there is change in IYC pattern that might be because of the new normal of market condition, anxious investor, or something else, hence it created the discourse among market stakeholder whether it remain a reliable prediction model or not. The research will focus on discourse among important economic stakeholders in US market and how they might impact on stock market rationally or irrationally using discourses network analysis, graph analysis, and t-Test analysis. The result confirmed that there is a different pattern on IYC, also there is a short-term correlation between IYC and stock price movement, confirmed the information theory.